Akibat Hukum Peraturan Daerah Sumatera Barat Tentang Penyelenggaraan Wisata Halal Dalam Meningkatkan Investasi Lokal - Ulfanora Nanda; Dian Amelia; Nanda Utama; Arya Putra Rizal Pratama (Media Iuris, 2023)
Abstract Structuring the tourism sector is a concern for the Regional Government, especially in West Sumatra, which continues to develop halal tourism as a hall mark of adaik basandi syara’ syarak basandi Kitabullah. The role of the Government of West Sumatra has been seen in structuring Halal Tourism after the issuance of West Sumatera Provincial Regulation concerning Organizing Halal Tourism. Halal tourism is a set of additional services for amenities, attractions and accessibility that are intended and provided to meet the experiences, needs and desires of Muslim tourists and other tourists who need them.West Sumatra part of the preservation of halal products as well as the application of the upholding philosophy of Islamic and customary values as the foundation of the life of the Minangkabau. In implementing halal tourism, the Government of West Sumatra is responsible for developing Halal Tourism business including providing investment incentives, facilitating investment facilities, as well as facilitating infrastructure facilities in implementing Halal Tourism. The results of this study explain that Regional Regulation concerning the Implementation of Halal Tourism in general has been implemented by the government, with so far establishing halal tourism destinations, including the Baso Pagaruyung Palace in Tanah Datar, Twin Lakes in Solok Regency, and the Islamic Center in Padang. The concept of halal tourism is not to prescribe a place, but rather to provide additional services to tourists who prioritize Muslim tourists and other tourists who need it. Keywords: Halal Tourism; Additional Service; Local Economy.